2014
DOI: 10.2106/jbjs.m.01420
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Oversizing: Nerve-to-Nerve Tube Diameter Mismatch

Abstract: Accurate sizing of nerve conduits to the nerve-stump diameter improves nerve recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 29 publications
(29 reference statements)
1
27
0
Order By: Relevance
“…2,3,6,25 Few studies have been conducted for large diameter nerve repairs, and many have reported the inferiority of the use of any conduit in comparison with autografts. 3,6,7,34,35 In this study, we were able to demonstrate at least comparable results for segmental gaps of 10 mm with a conduit diameter of 1.5 mm. The need to study this model in larger gaps, with larger diameter nerves, is necessary to evaluate the UBM conduit’s potential against autografts in larger animals.…”
Section: Discussionsupporting
confidence: 63%
“…2,3,6,25 Few studies have been conducted for large diameter nerve repairs, and many have reported the inferiority of the use of any conduit in comparison with autografts. 3,6,7,34,35 In this study, we were able to demonstrate at least comparable results for segmental gaps of 10 mm with a conduit diameter of 1.5 mm. The need to study this model in larger gaps, with larger diameter nerves, is necessary to evaluate the UBM conduit’s potential against autografts in larger animals.…”
Section: Discussionsupporting
confidence: 63%
“…Cell migration within the fibrin matrix creates some linear bands-bands of Büngner-that steer the growth of the nerve cone [78,86]. The mechanism through which neurite growth cone forms within the lumen of the conduit depends on the volumetric ratio [87,88]. If the gap is too long or the diameter of the inner lumen is too large, the growth cables are too thin, and due to the fibrin matrix, the growth cone takes on an hourglass figure that affects axonal regeneration.…”
Section: Nerve Conduitsmentioning
confidence: 99%
“…With an interpositional graft, it is important to utilize a graft of similar diameter; however, even then, it is not possible to correctly match the proximal donor fascicles with the distal stump recipient. Furthermore, regenerating axons must cross two neurorrhaphy sites instead of only one.…”
Section: Management Of Severe Upper Extremity Traumamentioning
confidence: 99%